Dental briquettes - Turaev Alimzhan Bakhriddinovich; Shukurov Sherzod Shuhratovich; Makhmudov Gulomjon Alisherovich (Zien Journals, 2021)
Dentistry Braces are in fact only that part of the bracket system that is attached to the tooth, a bracket for attaching a steel arch (wire). In addition to auxiliary fittings (springs, ligatures, rings) for fixing and tensioning the wire, a bracket system is formed. The following article looks into the dental briquettes, their types and application
Keywords: Dental briquettes; metallic briquettes; vestibular; ligature